KARAKTERISTIK DAN MOTIVASI WISATAWAN EKOWISATA DI BALI (STUDI KASUS DI JARINGAN EKOWISATA DESA) - Roy Jaya Saragih, Wiwin; Sendra, I Made; Sasrawan Mananda, I GPB. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 3 No 1 (2015): Jurnal IPTA (July 2015)DO - 10.24843/IPTA.2015.v03.i01.p04)
This study discusses about tourist characteristic and motivation in Pelaga, Badung Regency, Sibetan, Karangasem Regency, and Tenganan, Karangasem Regency. These three villages were developed into ecotourism village by JED (Village Ecotourism Network). Ecotourism is a community- based tourism, enviromentally sound, and responsible for sustainability. By seeing the number of visitor in Pelaga Ecotourism Village which has yet to reach the target, this is the impact of marketing system is still very common conducted without regard to the characteristics and motivations of tourists. This research purposes is to know the tourist characteristic and motivation who visit Pelaga, Sibetan, and Tenganan Ecotourism Village. Data collection in this research is done by direct obeservation to Pelaga Village, Sibetan Village, and Tenganan Village. Deep interview with the manager of JED and then deep interview with the coordinator of JED in every village, and also deep interview with the tourist to know their motivation visit Pelaga Ecotourism Village. While also using literature study and documentation. The result of this research show that in term geographic characteristic the visitor in Pelaga, Sibetan, and Tenganan Village is come from various country namely USA , Australia, Thailand, Japan, Germany, Canada, Netherland, England, France, Norway, Belgium, Philippines, Italy, Singapore, Malaysia, Cambodia, China, Poland, East Timor, Finland, Korea. In term socio- demographic characteristic the tourist who visit Pelaga and Sibetan dominated by man and in productive age, while in Tenganan is dominated by women and in older age. The whole tourist in three villages are work in private or public sector, and high educational background. Most of tourists who visit, have the motivation to know the culture in three villages.
Keywords: Tourist Characteristic, Tourist Motivation, Eco-tourism, Village Ecotourism Network